2007
DOI: 10.1021/jf072363p
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Preventive Peptide Lunasin from Solanum nigrum L. Inhibits Acetylation of Core Histones H3 and H4 and Phosphorylation of Retinoblastoma Protein (Rb)

Abstract: Lunasin, a unique 43 amino acid, 4.8 kDa cancer-chemopreventive peptide initially reported in soybean and now found in barley and wheat, has been shown to be cancer-chemopreventive in mammalian cells and in a skin cancer mouse model against oncogenes and chemical carcinogens. To identify bioactive components in traditional herbal medicines and in search for new sources of lunasin, we report here the properties of lunasin from Solanum nigrum L. (SNL), a plant indigenous to northeast Asia. Lunasin was screened i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 35 publications
3
62
0
1
Order By: Relevance
“…However, natural agents have not been popularly accepted, primarily due to their poorly defined molecular mechanisms. One such little investigated agent is degalactotigonin (DGT), which is isolated from Solanum nigrum L. The extractions of Solanum nigrum L have anticancer properties in breast cancer, colon cancer, and prostate cancer while leaving normal cells unharmed (8)(9)(10)(11). Thus far, one study has shown growth-inhibitory effects of DGT on a cervical cell line (HeLa) and contraceptive potential but provided no detailed insights into the underlying molecular mechanisms (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, natural agents have not been popularly accepted, primarily due to their poorly defined molecular mechanisms. One such little investigated agent is degalactotigonin (DGT), which is isolated from Solanum nigrum L. The extractions of Solanum nigrum L have anticancer properties in breast cancer, colon cancer, and prostate cancer while leaving normal cells unharmed (8)(9)(10)(11). Thus far, one study has shown growth-inhibitory effects of DGT on a cervical cell line (HeLa) and contraceptive potential but provided no detailed insights into the underlying molecular mechanisms (12).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the decreased activity of histone acetyltransferases (HATs), including lysine acetyltransferase 2A/2B and p300, is consistent with the decreased incidence of cancer, including colorectal and breast cancer (47)(48)(49). In previous studies, lunasin was demonstrated to competitively inhibit HATs, thereby inhibiting acetylation and regulating the cell cycle (24,32). The underlying molecular mechanisms of the binding of lunasin to histones remain unclear; however, they may be associated with the helical structure formed by the amino acid residues at positions 23-31, and the specific spatial structure or orientation of lunasin (42).…”
Section: Molecular Mechanisms Of Lunasin In the Prevention And Treatmmentioning
confidence: 80%
“…Following acetylation of HATs, lunasin and HATs competitively deacetylate histones to terminate transcription, thus leading to apoptosis. Therefore, lunasin is involved in the destruction of acetylation-deacetylation kinetics of histones (32). Deacetylated histones are absent from wild-type cells, so lunasin was not able to disrupt the proliferation or cause the apoptosis of wild-type cells.…”
Section: Molecular Mechanisms Of Lunasin In the Prevention And Treatmmentioning
confidence: 99%
See 2 more Smart Citations